Mucormycosis in COVID-19 Patients: A Hospital-based Study - Gurung, Kishor; Pant, Prabesh; Pokhrel, Sandeep; Neupane, Dhan Raj; Gurung, Samjhana (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: Fungal infections are increasingly being seen and mucormycosis is increasingly being isolated in COVID-19 patients, especially in those needing prolonged hospitalization. This cross-sectional study was carried out to isolate different fungi and identify their species in COVID-19 patients admitted for more than one month.Methods: Sputum samples were taken from all the consecutive COVID-19 patients admitted in the hospital for more than one month and their health condition not improving despite the administration of antibiotics during May to July 2020. The samples were subjected to 10% KOH mount and Gram’s stain, and cultured onto Sabouraud Dextrose Agar. This was visualized under direct microscopy. Fungus was identified based on its morphology.Results: Out of the 100 patients enrolled during the study period, 74 were male and 26, female. The different species of fungi were isolated from eight samples (8%) out of which two cases were confirmed to be mucormycosis (2%).Conclusion: We conclude that fungal infections, including mucormycosis, are not uncommon in post-COVID patients with long-term hospital stay. We recommend that the investigation and identification of fungus may be routinely followed.